Preparing principals for action, leadership - Davis, Harold S (NASSP Bulletin, 1974)
Both the curricula and methodology of preparing principals is the subject of this article. Describing procedures that work, it will interest principals as well as professors of school administration. © 1974, Sage Publications. All rights reserved.
Keywords: dept.edu

Modern Approaches to School Organization. - Davis, Harold S. (MSS Information Corp, 1974)
Keywords: School management and organization; United States; dept.adm; faculty_collection